Pengelolaan Pemanfaatan Arang Tempurung Kelapa Menjadi Briket Sederhana - Alfian Yusuf Saksono; Tatik Yuniarti; Saepudin Saepudin (IKRA-ITH ABDIMAS, 2023)
Along with the reduced reserves of energy sourced from fossils, making dependence on oil andgas fuels must be shifted to alternative energy. Furthermore, Karawang Regency has a coastline of84.23 Km in each coastal area, which the yard of its residents' houses is overgrown with coconuttrees. Coconut shell is a solid waste from processed coconut which has been taken from the coconutmeat. However, there are still many people who do not know how to manage it, so they just cast itaway. By educating and outreaching to the community, especially the youth on how to managecoconut shells into briquettes, it is hoped that they will know more about how to manage waste intosomething that has a selling price. The use of coconut shell charcoal briquettes is in line with thesolution to current global problems related to pollution, alternative energy and environmentallyfriendly technology. The training started from collecting coconut shells,to molding and drying.Increasing understanding and awareness through training in making simple briquettes is expectedto have an impact on young people being able to know and also have ideas to later open up businessopportunities that can advance the economy in the areas they live in.